2022
DOI: 10.1002/anie.202210012
|View full text |Cite
|
Sign up to set email alerts
|

From a Metal–Organic Square to a Robust and Regenerable Supramolecular Self‐assembly for Methane Purification

Abstract: Porous supramolecular assemblies constructed by noncovalent interactions are promising for adsorptive purification of methane because of their easy regeneration. However, the poor stability arising from the weak noncovalent interactions has obstructed their practical applications. Here, we report a robust and easily regenerated polyhedron-based cationic framework assembled from a metal-organic square. This material exhibits a very low affinity for CH 4 and N 2 , but captures other competing gases (e.g. C 2 H 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Presently, human’s dependence on fossil energy causes excessive emissions of greenhouse gas especially carbon dioxide (CO 2 ) and leads to irreversible climate change. Thus, new clean energy sources are urgently desired to alleviate this excessive carbon emission. Natural gas is a significant clean energy source that is mainly composed of CH 4 which endows it with a high hydrogen to carbon ratio and high energy density of 55.5 MJ·kg –1 . Besides, raw natural gas also contains a small quantity (∼20%) of variable amounts of impurities, such as C 2 H 6 , C 3 H 8 , and so forth. Among them, C 2 H 6 and C 3 H 8 are usually used as the feedstocks to produce higher value-added olefins (C 2 H 4 and C 3 H 6 ), which are usually used as the building blocks to synthesize polyethylene or polypropylene-based materials. Consequently, separating natural gas to obtain high-purity CH 4 and other remaining alkanes is of great importance to realize the efficient utilization of natural gas. Nowadays, the upgrading and purification techniques of light hydrocarbons are mainly achieved by extraction and cryogenic distillation, requiring large energy consumption that does not match the requirements of sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, human’s dependence on fossil energy causes excessive emissions of greenhouse gas especially carbon dioxide (CO 2 ) and leads to irreversible climate change. Thus, new clean energy sources are urgently desired to alleviate this excessive carbon emission. Natural gas is a significant clean energy source that is mainly composed of CH 4 which endows it with a high hydrogen to carbon ratio and high energy density of 55.5 MJ·kg –1 . Besides, raw natural gas also contains a small quantity (∼20%) of variable amounts of impurities, such as C 2 H 6 , C 3 H 8 , and so forth. Among them, C 2 H 6 and C 3 H 8 are usually used as the feedstocks to produce higher value-added olefins (C 2 H 4 and C 3 H 6 ), which are usually used as the building blocks to synthesize polyethylene or polypropylene-based materials. Consequently, separating natural gas to obtain high-purity CH 4 and other remaining alkanes is of great importance to realize the efficient utilization of natural gas. Nowadays, the upgrading and purification techniques of light hydrocarbons are mainly achieved by extraction and cryogenic distillation, requiring large energy consumption that does not match the requirements of sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…As methane is widely deployed in infrastructure for storage, distribution, and utilization and is easily isolated from the electrolyte and capture agents in the reaction mixture, , we thought that the performance of carbon-neutral methanation from a dilute CO 2 source was an attractive way to adopt the integrated electrocatalysis for the industrial-scale applications. To this end, we devised an enzyme-inspired approach that utilized highly positively charged and redox-reversible metal–organic macrocycles H1 with amide/amine groups to interact with the CO 2 adducts and intermediates for thorough reduction.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Correspondingly, a large number of studies have shown that the MOF is a potential self-sacricing template for the preparation of nanomaterials and has been widely used in chemical sensors, drug delivery, and electrocatalysis. [15][16][17] In particular, MOFderived transition metal-nitrocarbon (M-N x -C) nanomaterials are considered to be promising candidates for promoting the catalytic kinetics of the ORR and OER. [18][19][20] On the one hand, M-N x -C active sites derived from MOF precursors show excellent ORR activity; on the other hand, some metals are oxidized to high-value metal species (Fe 3+ , Ni 3+ ) as the real active sites of the OER, providing excellent OER activity.…”
Section: Introductionmentioning
confidence: 99%